1985
DOI: 10.1038/hdy.1985.67
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gene-environment interaction on the expression of longevity

Abstract: Several previous attempts at selecting for increased life span with Drosophila have failed to obtain a response to selection, and postulate that life span is controlled by non-genetic maternal effects instead of genes. In other experiments, however, populations have responded. This study uses a set of true-breeding long-and short-lived stocks developed by in Vitro selection to examine the effect on life span of developmental environment and outcrossing.The expression of genes for life span is shown here to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(77 citation statements)
references
References 18 publications
8
68
1
Order By: Relevance
“…This study, and that of Clare and Luckinbill (1985) show that selection for reproduction late in life can increase longevity, as theory predicts, and also that powerful gene-environment interactions influence adult life span and consequently, the effectiveness of selection. The inability of preceding studies to obtain sensible results during selection appears to have resulted from the artifactual introduction of these gene-environment interactions by controlling the density of developing populations to low levels.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study, and that of Clare and Luckinbill (1985) show that selection for reproduction late in life can increase longevity, as theory predicts, and also that powerful gene-environment interactions influence adult life span and consequently, the effectiveness of selection. The inability of preceding studies to obtain sensible results during selection appears to have resulted from the artifactual introduction of these gene-environment interactions by controlling the density of developing populations to low levels.…”
Section: Discussionsupporting
confidence: 64%
“…That is, the same genotype should manifest highly different phenotypes when raised at different developmental densities. Clare and Luckinbill (1985) have tested these predictions using the strains of this study. Their results show that in the stressful, uncontrolleddensity environment, the phenotype of F1 individuals is additively distributed, and intermediate between long-and short-lived parental lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, Curtsinger (1990) has shown that environmental effects are also very important in regulating the life span of Drosophila. Indeed, Clare and Luckinbill (1985) have previously reported the existence of a gene-environment interaction for the L strain, a phenomenon which was later confirmed by us (Wells et al, 1987). The mechanism of this gene-environment interaction is to date unknown.…”
mentioning
confidence: 52%
“…Our selected strains, which were originally derived from wild-caught flies, also exhibit an obvious larval density-dependent longevity (Clare & Luckinbill, 1985;Wells etal., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In the former experiments the stress level was higher than in the latter, because competition between larvae occurred. Based upon data of Clare & Luckinbill (1985), some stress from competition appears necessary to obtain a response to selection (Parsons, 1987), and hence the negative correlations expected under antagonistic pleiotropy.…”
Section: Introductionmentioning
confidence: 99%